Development and application of a numerically efficient model describing a rotary hearth furnace using CFD. (1st August 2019) - Landfahrer, M.; Schluckner, C.; Prieler, R.; Gerhardter, H.; Zmek, T.; Klarner, J.; Hochenauer, C.
Abstract: A computationally highly efficient numerical model is presented able to characterize combustion and steel heating in a real-size industrial rotary hearth furnace using computational fluid dynamics (CFD). High degree of accuracy, as well as high spatial and temporal resolution, can be achieved by the usage of an iterative scheme minimizing computational effort needed. Further increase in efficiency was achieved by selection of the most suitable combustion model. In this, the steady laminar flamelet (SFM), the eddy dissipation model (EDM) and the eddy-dissipation concept model (EDC) were used. Compared to other publications, the flamelet generated manifold (FGM) was also considered in this work. The models reveal minor differences in the calculated results, however, big differences occur in terms of computational effort required. The SFM, despite the usage of a detailed reaction mechanism, has been found as the most economic. The results revealed a high consistency with measurements verifying the high quality of the presented model. Also a scale formation model applied to the simulation reveals good agreement with measurements. In addition, two of the main problems of the present furnace are evaluated and suggestions for improvement are provided. Thus it is valuable for researchers and furnace operators at the same time. Highlights: Development of a highly accurate and computational inexpensive model for RHFs. Evaluation of combustion models with regard to accuracy and computational time. Extensive validating and Verifying by several measurement techniques used. Demonstrate block's scale formation and furnace's thermally stressed areas.